Effect of Microbial inoculation in combating the aluminium toxicity effect on growth of Zea mays - Arora, P.; Singh, G.; Tiwari, A. (Cellular and Molecular Biology, 2017)
The present study is aimed at improving the aluminium tolerance in maize crop employing the potential of microbial inoculants in conferring resistance to these toxicities via production of certain chelating compounds like siderophores, exopolysachharides and organic acids. Acid soils have now-a-days become one of the key factors for limiting growth of many agriculturally important crops. Aluminium is one of the major elements present in acid soils and is mainly responsible for toxicity in the soil. This aluminium is rapidly soluble in soil water and hence absorbed by plant roots under conditions where soil pH is below 5. This toxicity leads to severe root growth inhibition, thereby limiting the production of maize crops. It was observed that use of microbial inoculums can be helpful in elimination of these toxic compounds and prevent the inhibition of root growth . It was found that the soils contaminated with aluminium toxicity decreased the root length of maize plant significantly by 65% but Bacillus and Burkholderia inoculation increased this root length significantly by 1.4- folds and 2- folds respectively thereby combating the effect of aluminium toxicity. Aluminium concentration was found maximum in roots of plants which were grown under aluminium stress condition. But this aluminium accumulation decreased Ì´ 2-folds when Burkholderia was used as seed inoculants under aluminium stress conditions. Also, at 60mM aluminium accumulation, phosphorus solubilisation in roots was found to be increased upto 30% on Burkholderia inoculation. However, Bacillus inoculation didn’t show any significant difference in either of the case. Thus, the inoculation of seeds with Burkholderia isolates could prove to be a boon in sequestering aluminium toxicity in Zea mays.